Kinetic analysis of lead metabolism in healthy humans. - M B Rabinowitz; G W Wetherill; J D Kopple (The Journal of Clinical Investigation, 1976)
The steady state kinetics of lead metabolism were studied in five healthy men with stable isotope tracers. Subjects lived in a metabolic unit and ate constant low lead diets. Their intake was supplemented each day with 79–204 mug of enriched lead-204 as nitrate which was ingested with meals for 1–124 days. The concentration and isotopic composition of lead was determined serially in blood, urine, feces, and diet and less commonly in hair, nails, sweat, bone, and alimentary tract secretions by isotopic dilution, mass spectrometric analysis. The data suggest a three compartmental model for lead metabolism. The first compartment encompasses blood and is 1.5–2.2 times larger than the blood mass. It contains approximately 1.7–2.0 mg of lead and has a mean life of 35 days. This pool is in direct communication with ingested lead, urinary lead, and pools two and three. The second compartment is largely composed of soft tissue, contains about 0.3–0.9 mg of lead, and has a mean life of approximately 40 days. This pool gives rise to lead in hair, nails, sweat, and salivary, gastric, pancreatic, and biliary secretions. Pool three resides primarily in the skeleton, contains the vast quantity of body lead, and has a very slow mean life. Bones appear to differ in their rates of lead turnover. Within the relatively small changes in blood lead observed in the present study, the transfer coefficients between the pools remained constant.